PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Siti Rafi'ah (2023)
This research was conducted to analyze the effect of the interpretation of good corporate governance on tax avoidance. The object of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 - 2021, with a total sample of 58 companies. This study uses a quantitative method using panel data. This study used quantitative methods using panel data. The data analysis technique used is the panel data estimation selection test, classic assumption test, multiple regression test, and hypothesis test with a significance of 5%. The results of this study indicate that executive compensation, executive characteristic, audit committee, institutional ownership, managerial ownership, foreign ownership has no effect on tax avoidance. However, foreign ownership has negative effect on tax avoidance Keywords: tax avoidance, executive compensation, executive characteristic, audit committee, institutional ownership, managerial ownership, foreign ownership.